(untitled) (European Bison Conservation Newsletter, 2022)
In January 2021, European bison came back to Janowskie Forests after few hundred years of absence. The project of reintroduction was developed by Janów Lubelski Forest District under the frame of the project: “Complex project of European bison protection in Poland”. After over one year it could be noticed that animals have adapted very well and behave as typical wild herd. Many measures were implemented before and after the reintroduction by forest employees and scientists Those actions aimed at maintaining proper food resources and monitoring the herd.